Algorithm for wind speed estimate with polarimetric radar - Авер’янова, Ю. А. (Proceedings of National Aviation University, 2013)
The connection of wind speed and drops behavior is substantiated as well as the drop behavior influence onto the polarization characteristics of electromagnetic waves. The expression to calculate the wind speed taking into account the Weber number for the critical regime of drop deformation is obtained. The critical regime of drop deformation is the regime when drop is divided into two parts. The dependency of critical wind speed on the drop diameter is calculated and shown. The concept o polarization spectrum that is introduced in the previous papers is used to estimate the dynamic processes in the atmosphere. At the moment when the drop is under the influence of the wind that is equal to the critical wind speed the drop will be divided into two parts. This process will be reflected as the appearance of the two equal components of polarization spectra of reflected electromagnetic waves at the orthogonal antennas of Doppler Polarimetric Radar. Owing the information about the correspondence of the polarization component energy level to the drop diameter it is possible to estimate the wind speed with the obtained dependency. The process of the wind speed estimate with polarimetric radar is presented with the developed common algorithm